Functional Change of Agricultural Land in Tabanan Regency,Bali (Case Study in Subak Jadi, Kediri District) - Angelina Yulandari; I Made Sudarma; Gede Mekse Korri Arisena (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
Tabanan Regency as a rice barn in Bali has also experienced land conversion, particularly rice fields area. The rapid financial expansion requires the development of various infrastructures so that the demand for agricultural land is more enormous. Kediri sub-district is one of the regions that experienced the conversion of agricultural area to non-agricultural which is adequately high in Tabanan Regency. The purpose of this study is to determine the development of the land conversation in the Tabanan Region, differences in farmer’s income that have done the land conversion and those who have not done it, and the components that influence land conversion. The sampling technique is taken by proportional sampling with 40 people. The analysis techniques used are trend analysis, average difference test analysis, and logistic regression models. The result of the study concludes that the development of agricultural land conversion in Tabanan Regions is proceeding to extend. Based on the results of the t-test there is no significant difference between the average income of farmers who have done the land conversion and those who have not. Factors that influence the land conversion at the agricultural level are labor, number of dependents, irrigation systems, and surface area.